Wanprestasi "Tinjauan Yuridis terhadap Gugatan Wanprestasi dalam Hukum Acara Perdata: Studi Kasus di Pengadilan Jakarta Selatan": Penerapan teori hukum dalam kasus. - Micko Andira Ramadhan; Farhan Fadillah; Muhamad Dzulfikri; Muhammad Raya Fahreza; Muhammad Zaki Alhafiz; R Muhammad Ilhan Ma’ruf; Rizky Maulana Ardiansyah; Farahdinny Siswajanthy (Jurnal Sains Indonesia, 2025)
This research aims to examine juridically how default lawsuits are resolved through civil procedural law by taking a case study at the South Jakarta Court. The method used is descriptive qualitative, with data collection through the study of relevant primary, secondary, and tertiary legal literature. This study describes the process of civil procedural law in handling default lawsuits, including aspects of evidence, trial procedures, and the application of applicable legal principles. The results of the study show that the settlement of default lawsuits requires an in-depth understanding of legal procedures and principles of justice to ensure the protection of the rights of the parties. This research provides a comprehensive overview of the dynamics of default case settlement and its juridical implications in the practice of civil procedural law in Indonesia.